(untitled) (Computer systems and information technologies, 2022)
Breast cancer is the most common pathology among women. The death rate from breast cancer among women remains high. Early diagnosis and individual therapy are effective ways to extend people’s lives. The main diagnostic methods are cytological, histological, and immunohistochemical. The cytological method allows assessing the qualitative and quantitative changes in cells, as well as identifying extra- and intracellular inclusions and microorganisms. The histological method allows you to explore changes in the location of groups of cells in a particular tissue. The immunohistochemical method is based on the use of biomarkers. Immunohistochemical images are the result of an immunohistochemical investigation. The aim of the work is to develop a database of immunohistological images of breast cancer. With the developed database, a database design methodology was used, including infological, datalogical and physical design. The scientific novelty lies in the use of an object-oriented approach for designing a database of immunohistochemical images. The practical value of the work lies in the development of all stages of database design. As a result, an infological model, a data model, and a UML database diagram have been developed. For the practical implementation of the server part of the database, operating systems such as Windows / Linux / macOS can be used, the database server is MySQL. The developed breast cancer database contains more than 500 images for four diagnoses. The image resolution is 4096 x 3286 pixels. For each image, two features are given: relative area and brightness level. The developed HI&IHCIDB database has medium volume, high resolution, and quantitative characteristics in the description of immunohistochemical images